MOLECULAR CHARACTERISTICS OF ACID AND PEPSIN SOLUBLE COLLAGENS FROM THE SCALES OF GOLDEN CARP (PROBARBUS JULLIENI) - Ali, Ali Muhammed Moula; Benjakul, Soottawat; Kishimura, Hideki (Emirates Journal of Food and Agriculture, 2017)
Acid soluble collagen (ASC) and pepsin soluble collagen (PSC) were isolated from the scales of golden carp (Probarbus jullieni). Both ASC and PSC, identified as type I collagen, contained α- and β-chains as the dominant constituents. ASC and PSC had the yields of 0.42 and 1.16 g 100 g‒1 (dry weight basis), respectively. Amino acid composition revealed that glycine constituted 1/3 of total amino acid residues and no cysteine was found. ASC and PSC had imino acid contents of 197 and 202 residues/1000 residues, respectively. Fourier transform infrared spectroscopy (FTIR) and circular dichroism (CD) spectra indicated high integrity of the triple helical structure of both collagens. Based on differential scanning calorimetry (DSC), ASC and PSC had Tmax of 37.67 and 37.83 °C, respectively. Both collagens exhibited high solubility in acidic pH range (1‒3) and the decrease in solubility was found in the presence of NaCl at concentrations above 30 g L‒1. The overall results demonstrated that scales of golden carp could serve as another source of collagen.